The social ecology of religion - Reynolds, Vernon; Tanner, Ralph E.S., 1921- (New York : Oxford University Press, 1995)
Revised and updated edition of: The biology of religion, 1983.
Includes bibliographical references and index.
Keywords: Experience (Religion); Life cycle, Human -- Religious aspects; Sociobiology -- Religious aspects; Religions